The Role of Nitric Oxide in the Electrical Field Stimulation-Induced Contractions of Sphincter of Oddi and Gallbladder Strips in Guinea Pigs - Gultekin Hulya; Erdem S. Remzi; Emre-Aydingoz Selda; Tuncer Meral (Elsevier, 2006)
Abstract.: The aim of this study was to investigate the modulatory role of nitric oxide (NO) in the electrical field stimulation (EFS)-induced contractions of isolated sphincter of Oddi (SO) and gallbladder strips from guinea pigs. EFS was used to activate the intrinsic nerves in SO and gallbladder strips. EFS produced frequency-dependent biphasic contractile responses in the SO strips. A smaller contraction, "on response", occurred during EFS, which was followed by a bigger contraction, "off response". Both responses were completely and irreversibly abolished by tetrodotoxin (TTX) (10−6 M). Atropine (10−6 M) inhibited the "on response", but not the "off response". EFS produced frequency-dependent monophasic contractile responses in gallbladder strips, which were completely and irreversibly abolished by TTX (10−6 M) and atropine (10−6 M). A nitric oxide synthase (NOS) inhibitor, NG-nitro-L-arginine (10−4 M and 3 × 10−4 M, in SO and gallbladder strips, respectively), significantly increased all EFS-induced contractions of SO and gallbladder strips. L-Arginine, but not D-arginine reversed the effect induced by the NOS inhibitor, at all frequencies, in both strips. These results suggested that NO released from nitrergic nerve endings might play a regulatory role in the cholinergic neurotransmission of guinea pig SO and gallbladder strips. The "off response" in the SO preparations might be a rebound increase that was modulated by the nonadrenergic, noncholinergic inhibitory mediator NO. Keywords:: sphincter of Oddi, gallbladder, nitric oxide, electrical field stimulation, NG-nitro-L-arginine